Lavender Essential Oil as an Adjuvant Therapy for Anxiety Disorders - Chambali, Zafira Aliya Shafwa Putri; Algristian, Hafid (Yayasan Sinergi Kawula Muda, 2025)
With more than 301 million sufferers worldwide, anxiety disorders have become one of the most widespread mental health difficulties that frequently seek accessible and effective treatment alternatives. Anxiety results from the brain's response to a stimulus or perceived threat that a person will attempt to avoid. The limitless potential of lavender essential oil (Lavandula angustifolia) as an adjuvant therapy for anxiety disorders is investigated in this study, emphasizing the anxiolytic qualities and mechanisms of action of the oil. Data were collected from electronic sources like PubMed, Google Scholar, and Scopus, using a literature review methodology after a thorough literature search, emphasizing studies released in the previous ten years. The results suggest that lavender essential oil regulates the limbic system, especially the amygdala, as a central emotional response. It targets GABA activity and affects monoamine neurotransmitters, mainly through its active components, linalool and linalyl acetate. The most efficient method of delivery was inhalation, which considerably reduced anxiety symptoms with minimum side effects. According to the study, lavender essential oil shows promise as a complementary therapy for anxiety, providing a safe, all-natural substitute for treating anxiety.